Familial hyperkalemic periodic paralysis caused by a mutation in the sodium channel gene - Ji-Yeon Han; June-Bum Kim (Korean Pediatric Society, 2011)
Familial hyperkalemic periodic paralysis (HYPP) is an autosomaldominant channelopathy characterized by transient and recurrent episodes of paralysis with concomitant hyperkalemia. Mutations in the skeletal muscle voltage-gated sodium channel gene SCN4A have been reported to be responsible for this disease. Here, we report the case of a 16-year-old girl with HYPP whose mutational analysis revealed a heterozygous c.2111C>T substitution in the SCN4A gene leading to a Thr704Met mutation in the protein sequence. The parents were clinically unaffected and did not have a mutation in the SCN4A gene. A de novo SCN4A mutation for familial HYPP has not previously been reported. The patient did not respond to acetazolamide, but showed a marked improvement in paralytic symptoms upon treatment with hydrochlorothiazide. The findings in this case indicate that a de novo mutation needs to be considered when an isolated family member is found to have a HYPP phenotype.